Peran Pengetahuan dan Sikap Remaja Putri dalam Konsumsi Tablet Tambah Darah untuk Mencegah Anemia - Viona Amelia Putri; Nutrisia Nu’im Haiya; Iwan Ardian (Journal of Health, Medical, and Psychological Studies, 2026)
Anemia remains a major public health concern among adolescent girls and may adversely affect physical growth, learning concentration, and future reproductive health. In Indonesia, one of the primary preventive strategies is the school-based iron tablet supplementation program, whose effectiveness is closely related to adolescents’ knowledge and attitudes toward anemia prevention. This study examined the relationship between knowledge and attitudes and anemia prevention efforts among adolescent girls at SMP Negeri 20 Semarang. A quantitative correlational design with a cross-sectional approach was applied, involving 130 adolescent girls selected through total sampling. Data were collected using structured questionnaires measuring knowledge, attitudes, and anemia prevention efforts and were analyzed using the Chi-Square test. The findings demonstrated a significant relationship between knowledge and anemia prevention efforts (p = 0.009) as well as between attitudes and anemia prevention efforts (p = 0.001). Most respondents exhibited good knowledge levels (75.4%) and moderate attitudes (56.9%), while anemia prevention efforts were predominantly categorized as moderate (62.3%). These results indicate that adequate knowledge and positive attitudes contribute substantially to the adoption of anemia prevention behaviors, emphasizing the importance of continuous health education, school-based interventions, and supportive environments to enhance preventive practices among adolescent girls.